Kilka uwag na temat przekształcania samodzielnego publicznego zakładu opieki zdrowotnej - Klisowska, Izabela (Comments on Transforming Independent Public Institution of Healthcare Units, 2006)
In the present legal order, the distinction of sp zoz into public and unpublic is of a great importance and it is made being based upon the distinction of the entity forming the institution. The basic form of running IPIOH are independent public institutions, which are mostly the council people. 'Privatization of IPIOH is not possible at the moment1.The privatization is understood as transformation of independent public institution into unpublic one. Institution "Replacement" is possible only through the liquidation of public institution. Each transformation of independent public institution of healthcare is a long-lasting process, and it requires involvement of many entities - the forming entity, the institution social board, trade unions, voivode, individuals of territorial council - and these often have different expectations. Most of "converting procedures" of the independent public institutions of healthcare didn't come into being as based upon legal regulations but upon ruling, doctrine or supervisory organs decree - voivodes, and this is the reason why practice in this field is not uniform, in this process of widely understood transformations of independent public institution of healthcare liquidating them as well as uniting them is of a primary importance.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1103, s. 59-69